2017
DOI: 10.1103/physrevb.95.235418
|View full text |Cite
|
Sign up to set email alerts
|

Atomic discreteness and the nature of structural equilibrium in conductance histograms of electromigrated Cu nanocontacts

Abstract: We investigate the histograms of conductance values obtained during controlled electromigration thinning of Cu thin films. We focus on the question whether the most frequently observed conductance values, apparent as peaks in conductance histograms, can be attributed to the atomic structure of the wire. To this end we calculate the Fourier transform of the conductance histograms. We find all the frequencies matching the highly symmetric crystallographic directions of fcc-Cu. In addition, there are other freque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Therefore, we conclude that already at values around 15G 0 it is essentially only one junction that is conducting. Such instabilities seem to be characteristic to the EM process, since they are commonly not observed in MCBJ experiments but have also been found in recent EM experiments with Cu nanocontacts [24]. Since a distribution of contacts of various sizes exist, there is still a small probability for conductance through more than one channel that is reflected by the small number of counts in the range between 14G 0 and 5G 0 .…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Therefore, we conclude that already at values around 15G 0 it is essentially only one junction that is conducting. Such instabilities seem to be characteristic to the EM process, since they are commonly not observed in MCBJ experiments but have also been found in recent EM experiments with Cu nanocontacts [24]. Since a distribution of contacts of various sizes exist, there is still a small probability for conductance through more than one channel that is reflected by the small number of counts in the range between 14G 0 and 5G 0 .…”
Section: Resultsmentioning
confidence: 63%
“…Peaks at 2.1G 0 , 2.6G 0 , 3.0G 0 , 3.8G 0 , 4.2G 0 , 4.6G 0 , 14.5G 0 and 15G 0 are observed. At this point it is not clear whether these values are the result of several contacts in parallel or stem from a single contact, since non-integer values of conductance are commonly observed also for single contacts [24,29,30], mainly due to asymmetric and slightly irregular shapes of the contact, in agreement with theoretical simulations [7].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Compared to low temperature studies, a larger number of sharp relevant peaks were observed in the same conductance interval with only limited broadening by thermal effects or by the change of the applied voltage. Different periodicities in the conductance have been observed and have been assigned to different crystallographic orientations of the nanocontacts [7,10]. Both work-hardening and electromigration lead to enhanced local heating increasing the probability of the nanocontact to find structural equilibrium [10].…”
Section: Introductionmentioning
confidence: 98%
“…Different periodicities in the conductance have been observed and have been assigned to different crystallographic orientations of the nanocontacts [7,10]. Both work-hardening and electromigration lead to enhanced local heating increasing the probability of the nanocontact to find structural equilibrium [10]. In this way the structural properties of the nanocontacts are enhanced compared to methods based on pulling at low temperature.…”
Section: Introductionmentioning
confidence: 99%